Analysis of Language Errors in Thesis Proposal Writing - Andi Nurfaizah (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Language errors are inherent occurrences in every use of language, both orally and in writing. Good writing skills are important because they play a key role in enhancing students' academic quality and serve as a reflection of the educational institution. This study aims to analyze and identify language errors in the thesis proposal writing of students from the Faculty of Tarbiyah at the State Islamic University Datokarama Palu. The focus of the research is on the use of the fifth edition of the Enhanced Spelling System (EYD) as the main guideline, given the importance of applying correct language rules in academic works. This research uses a qualitative approach with a library research method to explore various types of common language errors, such as errors in punctuation usage, letter writing, word spelling, word choice, and sentence structure. The data sources for this research include sample thesis proposals from students, which are analyzed in-depth based on the fifth edition of the EYD guideline. The findings show that language errors are still prevalent, particularly in the use of punctuation, letter writing, consistency in word spelling, and sentence structure, which can affect the clarity and validity of academic arguments. Based on these findings, it is expected that this research can serve as a reference for supervisors and students to improve language quality in academic writing. Additionally, this study contributes to enriching the literature related to grammar and the application of the fifth edition of the EYD in the academic environment.